Generation, characterisation and solidification of crystalline microfoams - Van der Net, Antje (Trinity College (Dublin, Ireland). School of Physics, 2008)
This study is centered around the spontaneous ordering of equally sized microbubbles on top of a liquid pool, forming wet crystalline microfoams. This type of ordering was firstly observed by Bragg and Nye in 1947 and only recently taken up for further research. With the technique 'micro fluidic flow focusing' we created equally sized bubbles ranging between 100 and 800 μm in diameter, using surfactant solution and nitrogen. We found, in agreement with the literature, a dripping and jetting regime, where the bubble diameter D depends on the orifice width Oω times a factor of 1.19 ± 0.20 and ratio of the gas and liquid flow rate Qg, Qi to the power of 0.33 ± 0.06. Orifice length, surfactant choice and viscosity in a flow rate controlled device do not influence the bubble size. We observed a 'squeezing regime' at low gas and liquid flow rates hindering the microbubble generation, dependent on the entrance geometry, with bubbles created in the order of mm. T his points out that geometry plays a role in the performance of the bubble generator and should be further investigated in the future.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin